Delay discounting: concepts and measures - Matta, Adriana da; Gonçalves, Fábio Leyser [UNESP]; Bizarro, Lisiane (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), 2012)
Delay discounting, one element which underlies decision-making, can be defined as the depreciation of the value of a reward related to the time that it takes to be released. High rates of delay discounting are found in subjects who are willing to forgo greater rewards available only after some length of time and who show a preference for smaller rewards that are available immediately. Widely used as a measure of impulsiveness, delay discounting can be evaluated using experimental tasks. The present review evaluated tasks of delay discounting, their features, measures of evaluation and anomalies, and some variables that can affect delay discounting results and applications in the study of individual and intra-individual differences.
Keywords: delay discounting; decision making; impulsiveness; experimental tasks